2002
DOI: 10.1200/jco.20.6.1467
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum HER-2/neu Level Predicts Decreased Response to Hormone Therapy in Metastatic Breast Cancer

Abstract: Patients with ER(+) and serum HER-2/neu-positive metastatic breast cancer are less likely to respond to hormone treatment and have a shorter duration of response than ER(+) and serum HER-2/neu-negative patients. Their survival duration is also shorter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 17 publications
1
100
0
2
Order By: Relevance
“…HER-2 expression was evaluated with different methods: immunohistochemical detection of the p185 protein (13,18,19,22,24), evaluation of gene amplification by Southern blot (14,19) and ELISA (16,20,21,23,26), or chemoluminescent immunoassay (17) determination of circulating levels of HER-2 in the patient serum. Differences in the cutoff values chosen to distinguish between negative and positive HER-2 status complicate the picture even further, so that each study used its own particular methodology.…”
Section: Resultsmentioning
confidence: 99%
“…HER-2 expression was evaluated with different methods: immunohistochemical detection of the p185 protein (13,18,19,22,24), evaluation of gene amplification by Southern blot (14,19) and ELISA (16,20,21,23,26), or chemoluminescent immunoassay (17) determination of circulating levels of HER-2 in the patient serum. Differences in the cutoff values chosen to distinguish between negative and positive HER-2 status complicate the picture even further, so that each study used its own particular methodology.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Other studies have shown that patients with high levels of HER-2 have significantly poorer progression-free and overall survival using either high-dose chemotherapy, 7,8 or standard chemotherapy. 6 These results suggest that it is important to evaluate HER-2 levels in treatment trials for breast cancer to determine appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Overexpression of the HER-2 proto-oncogene in patients with node-positive and nodenegative breast cancer correlates with a poorer response and a reduced overall and progression-free survival in patients treated with hormone therapy, adjuvant radiotherapy, adjuvant and high-dose chemotherapy treatment regimens. [4][5][6][7][8] In general, HER-2 overexpression predicts for poor prognosis in breast cancer.…”
mentioning
confidence: 99%
“…Of the 11 studies in which serum HER-2/neu protein levels were tested for their ability to predict response to therapy, 8 (73%) of the studies found that elevated serum HER-2/neu protein levels predicted therapy resistance (8, 16 -18, 21), whereas three additional studies did not demonstrate this association (15,23,25). Serum HER-2/neu levels have correlated with decreased survival and absence of clinical response to hormonal therapy in estrogen receptor (ER)-positive tumors in some studies (13,21), but not in others (23). Serum HER-2/neu protein measurements have successfully predicted resistance to high-dose chemotherapy (16 -18), bone marrow transplantation (17), and response to trastuzumab single agent and combination treatment for metastatic HER-2/neu-positive disease (26 -29).…”
Section: Serum Her-2/neu Antigen Levels As a Tumor Marker-mentioning
confidence: 99%